Delimitation and description of the immature stages of a pollinating fig wasp, Ceratosolen solmsi marchali Mayr (Hymenoptera: Agaonidae). Issue 2 (29th November 2013) - Jia, Ling-Yi; Xiao, Jin-Hua; Niu, Li-Ming; Ma, Guang-Chang; Fu, Yue-Guan; Dunn, Derek W.; Huang, Da-Wei
Abstract: The mutualism between fig trees and their wasp pollinators is a model system for many ecological and evolutionary studies. However, the immature stages of pollinating fig wasps have rarely been studied. We monitored developing fig wasps of known ages and performed a series of dissections at 24 h intervals to identify key developmental traits of Ceratosolen solmsi marchali Mayr (Hymenoptera: Agaonidae), a pollinator of Ficus hispida L. (Moraceae). We identified where in the Ficus ovary eggs were deposited and time to hatch. We were also able to identify the timing and key underlying characters of five larval instars, three sub-pupal stages, and a single prepupal stage. We provide detailed morphological descriptions for the key stages and report some behavioral observations of the wasps in the several developmental stages we recorded. Scanning electron microscope images were taken.